China and the Globalization of Biomedicine - Zhang, Daqing, 1959-; Schneider, William H. (William Howard), 1945-; Luesink, David, 1974- (Book collections on Project MUSE., 2019)
"Argues that developments in biomedicine in China should be at the center of our understanding of biomedicine, not at the periphery"--